Otakar Kubín - Siblík, Jiří, 1912-2004 (Odeon, 1980)
Životopisná data a výklad umělcovy tvorby, doplněné reprodukcemi jeho děl.
Výběr z lit
Sez. vyobrazení
Keywords: Kubín, Otakar, -- 1883-1969; malířství; obrazové publikace